Mastering BeagleBone robotics: master the power of the BeagleBone black to maximize your robot-building skills and create awesome projects - Grimmett, Richard (Community experience distilled., 2014)
Robots are quickly bursting from the world of science fiction right into our own living rooms. The small-but-mighty BeagleBone Black embedded processor provides the power and capability to program your own robotic projects using its complete Linux development environment. Mastering BeagleBone Robotics lets you push your creativity to the limit through complex, diverse, and fascinating robotic projects right from scratch. Start off simple by building a tracked robot that moves, sees its environment, and navigates barriers. Go aquatic with a sailing robot that controls its rudder and sail, senses the direction of the wind, and plots its course using GPS. Then plunge beneath the surface of the waves as you create and control a robotic submarine to explore the world underwater with a webcam link. Walk on all fours with a limbed creation, and take to the skies as you create a quadcopter, then use the BeagleBone Black to make it autonomous and fly in its own direction using its own power.